Systematic Review of Video Education in Underrepresented Minority Cancer Survivors. Issue 4 (July 2020) - Hirschey, Rachel; Bryant, Ashley Leak; Walker, Jennifer S.; Nolan, Timiya S.
Abstract : Background: Underrepresented minority (URM) cancer survivors experience disparities in mortality and quality of life, compared with non-Hispanic whites. Disparities are associated with poor social determinants of health, enhanced by mistrust of the healthcare system. Trust can be facilitated by provider-patient racial/ethnic concordance, yet URM survivors rarely experience concordance. Effective health communication is needed for this vulnerable population. Objective: The aim of this study was to systematically review evidence on the composition and utility of health education videos among adult URM survivors. Methods: Literature searches were conducted in Web of Science, Embase, PubMed, Cochrane, PsycInfo, and CINAHL databases. Articles that included adult URM cancer survivor samples and either described or tested a video intervention aimed to improve health outcomes were included. Two researchers independently screened articles for inclusion and quality appraisal and abstracted and synthesized relevant data to identify themes. Results: Eight articles, detailing 7 independent studies, met inclusion criteria. Quality appraisal of the included studies was fair to good. Six themes were identified: (1) video development with stakeholders, (2) focus on designing culturally appropriate videos, (3) in-clinic video delivery, (4) video intervention effects, (5) provider and URM survivors support video interventions, and (6) building trust through personal stories. Conclusions: Video interventions are well received by URMs and improve outcomes yet are underutilized. More rigorous studies are warranted to develop best practices for video development and application. Implications for Practice: Videos serve as an easy, effective tool to achieve favorable outcomes in the care of URM survivors. Abstract : Supplemental digital content is available in the text.